PENGARUH LATIHAN SPLIT TERHADAP EKSTENSI TUNGKAI PADA ATLET KARATE KUMITE PEMULA DOJO SD NEGERI 03 MINAS - Cindy Mustika Putri; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Based on the observations of researchers at the Dojo of SD Negeri 03 Minas and the results of interviews with coach Ardilah, where the beginner athletes of the Karate Dojo at SD Negeri 03 Minas, have shortcomings which are influenced by one of the factors of physical condition, namely the flexibility (flexibility) where the tone when carrying out the attack is flexibility of the legs. still lacking so that the opponent can anticipate by parrying his attacks and cannot earn points. The title that the researchers examined was